2003
DOI: 10.1089/10445470360516725
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Phototherapy to the Treatment of Episiotomies

Abstract: The work demonstrated high healing effects with minimum secondary complications in the treatment of episiotomies using a therapeutic laser at an energy density of 2 J/cm(2). The application of polarized light at an energy density of 5 J/cm(2) also exerted favorable therapeutic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 2 publications
0
24
0
11
Order By: Relevance
“…Previously, a wound healing study performed by Kymplova et al concluded a 670-nm laser pulsed at various frequencies (10, 25, and 50 Hz) promoted wound repair more than the CW light source [47]. In research on pain relief, Sushko et al found that both CW and PW modes of 670-nm laser delivery reduced the behavioral manifestations of somatic pain as compared to the controls, but the application of pulsed light (especially, at 10 and 8000 Hz) was more effective [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a wound healing study performed by Kymplova et al concluded a 670-nm laser pulsed at various frequencies (10, 25, and 50 Hz) promoted wound repair more than the CW light source [47]. In research on pain relief, Sushko et al found that both CW and PW modes of 670-nm laser delivery reduced the behavioral manifestations of somatic pain as compared to the controls, but the application of pulsed light (especially, at 10 and 8000 Hz) was more effective [48].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are corroborated by a controlled study conducted in the Czech Republic with 2,436 women with episiotomies, comparing the analgesic effects of phototherapy using three light sources, LLLT, a halogen light and a light-emitting diode (LED). It was concluded that LLLT was the best option and that it could be complemented by the application of halogen light (Kymplová et al, 2003). However, some methodological aspects of the research are questionable, such as the lack of randomisation, evaluation criteria, and a detailed description of the therapies' application and omitted details about possible conflicts of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The search for methods, especially non‐pharmacological methods, that relieve perineal pain and do not interfere with lactation has been a challenge for professionals who provide care for women during childbirth and the postpartum period. Two studies have investigated the effects of lasers on the relief of perineal pain, but these failed to provide conclusive results owing to methodological weaknesses, such as an absence of randomisation, a lack of standardisation of the evaluation criteria and of the dosage of the laser (Kymplová et al. 2003, Rzakylieva et al.…”
Section: Introductionmentioning
confidence: 99%